Dynamically accessible perturbations and magnetohydrodynamic stability - Hameiri, Eliezer (Physics of plasmas, 2003)
It is shown that restricting the perturbations of a magnetohydrodynamic plasma equilibrium state with flow to those that are dynamically accessible yields the same stability criterion as the one obtained by minimizing the plasma energy subject to given values of all constants of the motion. This criterion is sharper than the classical one, which is based on the second variation of the potential energy (δW).